PENGARUH ANALISIS RISIKO DAN KEPERCAYAAN TERHADAP KEMUDAHAN MELAKUKAN TRANSAKSI MELALUI ESCROW ACCOUNT TOKOPEDIA (STUDI KASUS SETIA JAYA MOTOR) - aldo firmansyah abdurrahman (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2023)
Tokopedia, an e-commerce platform. People who previously used digital applications have increased their efforts, while those who previously did not use them are now starting to use digital applications to fulfill their needs. One of the things consumers buy online is a risk. Another important factor influencing online shopping is convenience. In addition, another factor that influences the purchase of products from Tokopedia as an online medium is a belief. Research objectives 1) To find out if the risk variables have a significant effect on the ease of transactions via Tokopedia account (a case study of UMKM Setia Jaya Motor). 2) To find out if the Belief variable has a significant effect on the ease of transacting via Tokopedia account (a case study of UMKM Setia Jaya Motor). 3) To find out if the risk and belief variables have a significant effect on the ease of transacting via Tokopedia account (a case study of UMKM Setia Jaya Motor). From the results of testing the research hypothesis, there is a partiallyl significant effect between risk on Ease of Transactions Via Tokopedia Account. The partially significant influence between belief on Ease of Transactions Via Tokopedia Account. The simultaneous significant influence between risk and belief on Ease of Transactions Via Tokopedia Account.